Concentração de zinco e selênio em pacientes críticos segundo estratificação de gravidade - Ruocco, Marina Augusta Cirino [UNESP] (2015)
The Simplified Acute Physiology Score III (SAPS III) score is one of the scoring systems that estimates the rate of hospital mortality and predicts the severity of the patient, most recently used. News studies of critical ill patients have associated the use of the scoring systems to the evaluation of zinc (Zn) and selenium (Se) concentrations, as the severity of the patient interfere in the concentration of these micronutrients. Thus, this study presented a proposed stratify critically ill according to severity and analyzing the concentrations of zinc and selenium in plasma, erythrocytes, and urine. This was a mixed study, accomplished in the Intensive Care Unit (ICU) of the Hospital Estadual Américo Brasiliense/SP. Data were collected in the first hour before or after ICU hospitalization to fill score. Subsequently, 95 patients were evaluated for micronutrient analysis in groups identified by the severity and diagnosis of sepsis. The results showed that the SAPS III score has adequate calibration and discrimination for the population studied and the cut-off point that better discriminated survivors from non-survivors was 63.5 points. As regards the analysis of plasma concentrations, Zn and Se were lower than the reference values for both micronutrients (55.07±26.10mg / dl and 14.55±4.64mg/L, respectively) and higher the reference urinary Zn (2522.02±2340.46μg/24hours). The average plasma concentration of Se was significantly lower in patients with greater severity, which was not seen for Zn (p=0.921). The results albumin (r= -0.2628, p=0.0105) and CRP (r=0.3965, p<0.0001) correlated with the SAPS III severity score. It was concluded that changes in the concentrations of Zn and Se in plasma are common in critically ill patients and related to the severity for the Se.